ЫРЫМЛАР МЕНЕН БАЙЛАНЫСЛЫ ТИЛ БИРЛИКЛЕРИНИӉ ҮЙРЕНИЛИЎИНИӉ ТЕОРИЯЛЫҚ ТИЙКАРЛАРЫ ҲӘМ ОЛАРДЫӉ АНАЛИЗИ - Бегниязов, М.А. (SCIENCE and SOCIETY, 2024)
The article is devoted to the study of linguistic units in the Karakalpak tradition. At the same time there are considered studies conducted with the help of foreign scientists on issues of customs. Lexical units associated with traditions are divided into three types, studied and specified by identifying and directing target queries.
Keywords: traditions; customs; rituals; analysis; vocabulary